2021
DOI: 10.3390/metabo11050328
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Tock Consider the Clock: The Influence of Circadian and External Cycles on Time of Day Variation in the Human Metabolome—A Review

Abstract: The past decade has seen a large influx of work investigating time of day variation in different human biofluid and tissue metabolomes. The driver of this daily variation can be endogenous circadian rhythms driven by the central and/or peripheral clocks, or exogenous diurnal rhythms driven by behavioural and environmental cycles, which manifest as regular 24 h cycles of metabolite concentrations. This review, of all published studies to date, establishes the extent of daily variation with regard to the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 118 publications
(195 reference statements)
2
17
0
Order By: Relevance
“…However, the actigraphyderived sleep and wake times of our study population, as reported in Koshy et al (2019), suggest that the extent of sleep restriction due to night shift work was relatively small (i.e., on average less than 1 h) compared with previous studies, in which the sleep period was restricted to 4 h or less. Therefore, it is unlikely that sleep deprivation had a major impact on our results, a conclusion corroborated by a recent review that concluded that time of day has a larger impact than sleep disturbances on the urinary metabolome (Hancox et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the actigraphyderived sleep and wake times of our study population, as reported in Koshy et al (2019), suggest that the extent of sleep restriction due to night shift work was relatively small (i.e., on average less than 1 h) compared with previous studies, in which the sleep period was restricted to 4 h or less. Therefore, it is unlikely that sleep deprivation had a major impact on our results, a conclusion corroborated by a recent review that concluded that time of day has a larger impact than sleep disturbances on the urinary metabolome (Hancox et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…However, despite its practicality, an important point of consideration when using urine for these types of analyses is the need for a suitable normalization method to account for differences in urinary flow rate. Creatinine normalization is routinely used but less appropriate since creatinine excretion may display diurnal variation-although this was not observed in the current study-and show substantial interindividual variation (Hancox et al, 2021). Taking advantage of the fact that urine volumes and voiding times were precisely documented during both study visits, we were able to calculate the urinary flow rate of each sample and use this to normalize metabolomic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Much of our knowledge of the control of metabolism by circadian clocks and sleep in humans comes from metabolomics, the systematic study of small molecules produced by anabolic and catabolic reactions, which can be sampled periodically across the day from blood, urine, and saliva (Ang et al, 2012;Dallmann et al, 2012;Bell et al, 2013;Davies et al, 2014;Skene et al, 2018;Grant et al, 2019;Kervezee et al, 2019;Honma et al, 2020;Hancox et al, 2021). These have been complemented by sampling accessible tissues, such as blood and adipose tissue, across time and analyzing the temporal pattern of RNAs (transcriptomics) or proteins (proteomics) therein (Spo ¨rl et al, 2012;Robles and Mann, 2013;Archer et al, 2014;Christou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…GH was also found to be more variable compared with the other biomarkers, which is not surprising, as GH has been previously reported to have a high degree of ultradian and diurnal variability. [28] For this reason, GH was removed from consideration for inclusion in the algorithm.…”
Section: Diurnal Variabilitymentioning
confidence: 99%